(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The development of each branch of science requires preconditions for formation, which have different methodological bases. The preconditions for the development of pedagogical anthropological thought were formed in the folklore of the Armenian people. They give an opportunity to see what the development process was like and to predict the development prospectives.